2018
DOI: 10.1002/csr.1500
|View full text |Cite
|
Sign up to set email alerts
|

How are supply chains addressing their social responsibility dilemmas? Review of the last decade and a half

Abstract: Supply chain social responsibility is increasingly a pressing concern to organizations of all sizes.Justified by its impact on the bottom line, various measures were adopted for resolution and prevention. However, despite the abundance of literature on the topic, there continues to be a lack of evidence on which of the measures are the most prolific, that is, how the concern of interest is actually handled. Such evidence would highlight missed opportunities and set the stage for future research. Toward this go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The capacity of the environment (EN) determines a stable and lasting development of SC. Sustainable design (EN1) aims to increase building performance by minimizing adverse impacts on the environment as well as improving the health and comfort of building users (Basta, Lapalme, Paquet, Saint-Louis, & Abu Zwaida, 2018). Reducing pollution and waste (EN2) and efficient use of energy and resources (EN3) are effective measures to mitigate the environmental burden of the use of energy and resources (Zhu, Zhao, & Sarkis, 2011).…”
Section: Proposed Measuresmentioning
confidence: 99%
“…The capacity of the environment (EN) determines a stable and lasting development of SC. Sustainable design (EN1) aims to increase building performance by minimizing adverse impacts on the environment as well as improving the health and comfort of building users (Basta, Lapalme, Paquet, Saint-Louis, & Abu Zwaida, 2018). Reducing pollution and waste (EN2) and efficient use of energy and resources (EN3) are effective measures to mitigate the environmental burden of the use of energy and resources (Zhu, Zhao, & Sarkis, 2011).…”
Section: Proposed Measuresmentioning
confidence: 99%
“…In turn, the supply chain in the industry is responsible for aggravating air quality and global warming, and all the related firms of the supply chain are confronted with risks (e.g., from the supplier to the customers), which should be managed. Such management is consequently called the supply chain management (SCM; Basta, Lapalme, Paquet, Saint‐Louis, & Abu Zwaida, ). Accordingly, SCM is performing a wide variety of activities and is utilizing the utmost resources to yield services and products for customers (Omar, Davis‐Sramek, Fugate, & Mentzer, ), such as managing unsafe work places, misbehaving with employees, and damaging the environment (Basta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such management is consequently called the supply chain management (SCM; Basta, Lapalme, Paquet, Saint‐Louis, & Abu Zwaida, ). Accordingly, SCM is performing a wide variety of activities and is utilizing the utmost resources to yield services and products for customers (Omar, Davis‐Sramek, Fugate, & Mentzer, ), such as managing unsafe work places, misbehaving with employees, and damaging the environment (Basta et al, ). Managing these challenges forced the industry's executives to employ different sustainability practices (Mathivathanan et al, ; Veleva & Ellenbecker, ) to strike a balance between economy, society, and environment (Dev & Shankar, ; Diabat, Kannan, & Mathiyazhagan, ; Xu, Boh, Luo, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that providers may be in a better rival position according to increased involvement by buying directors in socially responsible activities and improving the situation as estimated by prize and potency. Cruz [28,29] discussed the influence of social responsibility on supply chain members with a multicultural decision-making method; Carter and Rogers [30] stressed that social issues should interfere with the operations management of supply chain members; Tate et al [31] showed that improving CSR performance of a supply chain may affect consumer choice, corporate image and reputation; Boehe and Cruz [32] further suggested that if a firm wants to protect their corporate image and enhance corporate reputation, then the firm must ensure that social responsibility applies to their supply chain; Hoejmose et al [33] explored that the impacts of social responsibility on supply chain, and found that low-cost manufacturers largely ignore social responsibility in supply chain management; and Basta et al [34] reviewed and analyzed 590 articles on a socially responsible supply chain and provided a clear understanding of this subject.…”
Section: Socially Responsible Supply Chainmentioning
confidence: 99%